KONTRIBUSI MINAT BACA DAN MOTIVASI BELAJAR TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 7 PADANG - Oktarilla, Annisa; Atmazaki, Atmazaki (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT The purpose of this research is three. First, describe the contribution of reading interest to the writing text description skills of class VII students of  SMP Negeri 7 Padang. Second, describe the contribution of learning motivation to the writing text description skills of class VII students of SMP Negeri 7 Padang. Third, describe the contribution of reading interest and learning motivation together towards writing text description skills of class VII students of SMP Negeri 7  Padang. The  type of this research is quantitative with descriptive methods. The design used in this research is correlational design. The population of this research was the seventh grade students of the SMP Negeri 7 Padang who were enrolled in the 2018/2019 school year, which was 251 students. The sample in this research was determined by simple random sampling using the Slovin formula from the population, which is 40 students. The data of this  research were scores on the results of filling in the reading interest questionnaire, the scores on the results of filling in the learning motivation questionnaire, and scores on the results of the test writing skills of the description text. The instrument of this research was a questionnaire to measure reading interest and student learning motivation and performance tests to measure description text writing skills. The results of this research are three. First, there is a contribution of reading interest towards the writing text description skills of 26,13%. Second, there is a contribution of learning motivation to the writing text description skills of 3,2%. Third, reading interest and learning motivation contribute to the writing text description skills of 30,25%.  Kata Kunci: Kontribusi, Minat Baca, Motivasi Belajar, Keterampilan Menulis Teks Deskripsi.